6th Annual Fresno County Young Lawyers Association Justice Hopper Memorial Luncheon; Speaker: San Francisco Superior Court Judge Ira Brown - Watkins, Howard::::::::: (1987)
Judge Ira Brown speaking on complex litigation re asbestos litigation Seated: Robert Sears, Howard Sagaser, Justice Donald Franson and ?